The Legality Of Cultivated Palm Oil, Research On The Readiness Of Small Holder Farmers In Indonesia To Produce Sustainable Palm Oil (ISPO) Is Reviewed - Apriyanto, Mulono; Azhar, Ali; Satriawan Fikri, KMS. Novyar; Puspitasari, Feni (International Journal of Business, Law, and Education, 2022)
The Indonesian government is working to ensure the sustainability of the country's palm oil industry through the establishment of a sustainability standard called Indonesian Sustainable Palm Oil (ISPO) in presidential regulation no. 44 of 2020. The purpose of this study is to determine the value of smallholders' ability to comply with Indonesia Sustainable Palm Oil (ISPO) standards based on the legality of farmers' land in Indragiri Hilir. By comparing the legality of cultivated land applied by independent farmers, the audit method is used to conduct a quantitative descriptive analysis of conformity with ispo principles, criteria, and indicators. The legal status of smallholder farmers' land is incomplete, as the majority of oil palm plantations are located in KBK and the majority of land lacks a certificate but does have a letter of compensation.